Coronaviruses in wastewater processes: Source, fate and potential risks (2020)
The last 17 years have seen three major outbreaks caused by coronaviruses, with the latest outbreak, COVID-19, declared a pandemic by the World Health Organization. The frequency of these outbreaks, their mortality and associated disruption to normal life calls for concerted efforts to understand their occurrence and fate in different environments. There is an increased interest in the occurrence of coronaviruses in wastewater from the perspective of wastewater-based epidemiology. However, there is no comprehensive review of the knowledge on coronavirus occurrence, fate and potential transmission in wastewater. This paper, provides a review of the literature on the occurrence of coronaviruses in wastewater treatment processes. We discuss the presence of viral RNA in feces as a result of diarrhoea caused by gastrointestinal infections. We also reviewed the literature on the presence, survival and potential removal of coronaviruses in common wastewater treatment processes. The detection of infectious viral particles in feces of patients raises questions on the potential risks of infection for people exposed to untreated sewage/wastewater. We, therefore, highlighted the potential risk of infection with coronaviruses for workers in wastewater treatment plants and the public that may be exposed through faulty plumbing or burst sewer networks. The mortalities and morbidities associated with the current COVID-19 pandemic warrants a much more focused research on the role of environments, such as wastewater and surface water, in disease transmission. The current wealth of knowledge on coronaviruses in wastewater based on the reviewed literature is scant and therefore calls for further studies.